IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TENTANG KEDUDUKAN ANAK LUAR KAWIN TERHADAP KOMPILASI HUKUM ISLAM - Indrabajra Aziiz, Candraditya; Dirksen, A. A. Gede Ngurah; Putra Atmadja, Ida Bagus (Kertha Semaya : Journal Ilmu Hukum, 2013)
With the the decision of the constitutional court number 46/PUU-VIII/2010 27thFebruar 2012 that gives a illegitimate child that he/she can prove if he/she is thebiological child of a person with DNA exam and other thing that can prove by sience,the decision above can make another legal result if the person is proven his/her father.The another legal result is the child is not only have a civil law relationship to hismother but also have a civil law relationship to his biological father to. In other lawthat Indonesia have, that is compilation of Islamic law no 1/1997 also rule thatillegimate child only have nasab relationship only by his mother.
Keywords: Illegitimate Child, Compilation of Islamic Law